2015
DOI: 10.1038/gim.2014.138
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–phenotype correlation and mutation spectrum in a large cohort of patients with inherited retinal dystrophy revealed by next-generation sequencing

Abstract: Purpose: Inherited retinal dystrophy (IRD) is a leading cause of blindness worldwide. Because of extreme genetic heterogeneity, the etiology and genotypic spectrum of IRD have not been clearly defined, and there is limited information on genotype-phenotype correlations. The purpose of this study was to elucidate the mutational spectrum and genotype-phenotype correlations of IRD. Methods:We developed a targeted panel of 164 known retinal disease genes, 88 candidate genes, and 32 retina-abundant microRNAs, used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
132
1
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 183 publications
(146 citation statements)
references
References 38 publications
10
132
1
3
Order By: Relevance
“…Table S1 online), and 1 patient was previously screened using WES. 16 No deleterious mutations were found in any of the 164 known genes, however, suggesting either that pathogenic mutations might have been missed by exome sequencing or that the clinical phenotype was caused by previously undescribed, novel RP genes.…”
Section: Results Study Subjectsmentioning
confidence: 98%
See 2 more Smart Citations
“…Table S1 online), and 1 patient was previously screened using WES. 16 No deleterious mutations were found in any of the 164 known genes, however, suggesting either that pathogenic mutations might have been missed by exome sequencing or that the clinical phenotype was caused by previously undescribed, novel RP genes.…”
Section: Results Study Subjectsmentioning
confidence: 98%
“…This strategy was validated in 50 unrelated patients with either simplex RP or XLRP, all of whom previously tested negative for pathogenic mutations by exome sequencing. 16 We assessed and compared the sequencing quality of entire targeted regions and ORF15, which demonstrated that ORF15 lies in a region of very low sequencing depth. Subsequent screening of ORF15 directly by Sanger sequencing resulted in the identification of pathogenic mutations in 7 of 50 patients (14%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 We also reexamined the pathogenicity using multiple other databases. 2 Our analyses indicate that this variant is predicted to be damaging by MutationTaster 6 (score 0.999) and PolyPhen-2 (ref. 7) (score 0.994).…”
mentioning
confidence: 99%
“…Our study was a large-scale screening investigation of patients with inherited retinal dystrophy. 2 We considered the two variants as damaging for the following reasons. (i) The first variant, E1086G, was reported as a known disease mutation in a previous study 3 and in the RetinoGenetics database 4 as well as the Human Gene Mutation Database (CM080033), the major database for human mutation repositories.…”
mentioning
confidence: 99%